3D Multiple Triangular Prisms for Highly Sensitive Non-Contact Mode Triboelectric Bending Sensors - Han, Gi Hyeon; Kim, Sun Woo; Kim, Jin Kyeom; Lee, Seung Hyun; Jeong, Myeong Hoon; Song, Hyun Cheol; Choi, Kyoung Jin; Baik, Jeong Min (MDPI, 2022)
Here, a highly sensitive triboelectric bending sensor in non-contact mode operation, less sensitive to strain, is demonstrated by designing multiple triangular prisms at both sides of the polydimethylsiloxane film. The sensor can detect bending in a strained condition (up to 20%) as well as bending direction with quite high linear sensitivity (similar to 0.12/degree) up to 120 degrees, due to the electrostatic induction effect between Al and poly (glycerol sebacate) methacrylate. Further increase of the bending angle to 135 degrees significantly increases the sensitivity to 0.16/degree, due to the contact electrification between them. The sensors are attached on the top and bottom side of the proximal interphalangeal and wrist, demonstrating a directional bending sensor with an enhanced sensitivity.